POTENSI DAN EFEKTIVITAS PENGELOLAAN ZAKAT FITRAH - Samsul Rizal; Irwan Abdullah; Sahrullah Sahrullah; Laila Nur Atika (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the potential and effectiveness of the management of Zakat Fitrah in South Sulawesi Province. The type of research used is descriptive qualitative. The results obtained in this study are the potential of Zakat Fitrah in South Sulawesi Province is very large. This is evidenced by the number of zakat fitrah collected, from the regency, city and provincial level, namely the amount of zakat fitrah collected during the Ramadhan yesterday in the May 2019 period. Specifically, the data available at the National Board of Education of the South Sulawesi Province BAZNAS is around Rp. 139,595,500 collected from the individual Muzakki and Muzakki Institution data. As for the total amount of zakat fitrah collected throughout the South Sulawesi Province, both at the Regency and City level, which is registered in the existing system at the National Amil Zakat Agency (BAZNAS) of South Sulawesi Province is around Rp. 29,896,902.304, -. While the effectiveness of zakat fitrah management in South Sulawesi Province is still in the effectiveness phase.